MEMBANGUN KEPERCAYAAN DIRI BERBICARA PADA MAHASISWA S1 KEPERAWATAN UNIVERSITAS MUHAMMADIYAH MAGELANG MELALUI APLIKASI ZELLO - Fidian, Athia (Universitas Muhammadiyah Magelang, 2016)
This research is aimed to describe whether the zello application significance or not in building the students’ speaking confidence.Besides, it is also aimed to know the zello application build the students’s English speaking confidence.This research used quantitative method where experimental is needed to gather the data. Therefore, two classes were choosen forthe experiment; the first class served as the experimental class, and the second class served as the control class. Quasi-experimentalwith non equivalent control group design was used as the design of the research. There were two classes, experimental classand control class but the treatment was only given to the experimental class. Pretest was given to both classes before theimplementation of the treatment. While the postest was held to find out the students speaking confidence achievement.Findings show that there were a significance of the zello application in building the nursing’s student confidence in speaking.From the result of this experiment, it was found that zello aplication can be used in building the nursing’s students confidencein speaking. English spoken language through an application, can encourage students in using English in communication. Asa result, students were active and tried to use the English language in discussing the task, while the traditional method didn’tmake a significance change.